2005
DOI: 10.5424/srf/2005142-00879
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of seed germination of Pinus sylvestris L. at its southern, Mediterranean distribution range

Abstract: Seed germination of Pinus sylvestris L. in south eastern Spain was studied under field and growth chamber conditions to assess the effect of the most representative microhabitats of these forests. Under growth chamber conditions, germination was high (almost 95%) in the litter from all microhabitats. Germination under field conditions was highest (up to 95%) in shade-free microhabitats and therefore higher soil temperature (e.g. areas of bare soil and meadows), and lowest (down to 62%) in microhabitats with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
27
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 37 publications
8
27
0
1
Order By: Relevance
“…Similar results were reported by Lucas-Borja et al (2011). However, Castro et al (2005) observed decreasing germination rates in dense stands of Pinus sylvestris in mountainous locations of the Iberian Peninsula. In our model selection process, a significantly positive influence of overstory competition (i.e.…”
Section: Ecological and Management Implicationssupporting
confidence: 78%
“…Similar results were reported by Lucas-Borja et al (2011). However, Castro et al (2005) observed decreasing germination rates in dense stands of Pinus sylvestris in mountainous locations of the Iberian Peninsula. In our model selection process, a significantly positive influence of overstory competition (i.e.…”
Section: Ecological and Management Implicationssupporting
confidence: 78%
“…Drought alleviation and higher water availability during 2013 allowed Spanish black pine to emerge without shrub and canopy cover protection (Castro et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Light on the forest floor is a direct consequence of canopy structure and stand/shrub density (Catovsky and Bazzaz 2000;Balandier et al 2006b;Barbier et al 2008); a high light level may increase soil temperature and climate demand, thus decreasing accordingly soil moisture by increasing soil evaporation, as recorded in this particularly difficult conditions under the lowest tree canopy cover (Table 2). Soil temperature and humidity are likely to be the two main drivers of germination and seedling emergence under field conditions (Lee et al 2004;Castro et al 2005;Del Cerro et al 2009). There is broad evidence (Holmgren et al 1997;Del Cerro et al 2009) that soil and air temperatures are lower under tree canopy, wind velocity is reduced and air humidity is higher than in open areas, thus reducing seedling transpiration demand and soil evaporation.…”
Section: Discussionmentioning
confidence: 99%
“…K. Tsitsoni (tsitsoni@for.auth.gr), Dept of Silviculture,Faculty of Forestry and Natural Environment,Aristotle Univ. of Thessaloniki,PO Box 262,Greece. ment, the seedling (Castro et al 2005). Pinus halepensis is characterized by a high germination capacity.…”
mentioning
confidence: 99%